Managing Circular Economy Barriers in Recycling Companies - Siregar, Dede Iskandar; Suandevin, Hichmaed Tachta Hinggo; Zaki, Hammam (SBM ITB, 2020)
Abstract: Circular Economy (CE) has recently attracted the attention of academics, governments and business people due to the concept which believed to be a solution to the negative impacts caused by the traditional economic system. Previous research examining this topic has generally dominated CE principles as the focus of an investigation. Another study also conducted a mapping of CE barriers which consisted of cultural, regulatory, market and technological factors. However, the focus of such studies often makes it difficult to determine how companies are implementing CE. This article aims to fill the gap by analyzing how recycling companies manage CE based on their saving factor. This study uses a qualitative case study approach in three companies located in Pekanbaru. The first two cases are waste managers made from cans, paper, plastics and organic waste, while the last case involves a used oil refining company. Data collection was done through desk evaluations, direct interviews, and document studies, while the analysis was utilized by using within-case and cross-case. The results show that CE implementation was carried out through several approaches including adopting a sharing economy system (between companies and customers), cooperating production of similar companies, and encouraging employee skills improvement through continuous training.Keywords: Circular Economy, barriers, strategies, case studies, recycling companiesÂ Abstrak: Ekonomi Melingkar (CE) belakangan banyak menyita perhatian akademisi, pemerintah maupun pebisnis dikarenakan konsep tersebut diyakini dapat menjadi solusi terhadap dampak negatip yang disebabkan oleh sistim ekonomi tradisional. Penelitian terdahulu yang mengkaji topik ini umumnya didominasi prinsip CE sebagai fokus penyelidikan. Studi lain juga melakukan pemetaan hambatan CE yang terdiri dari factor budaya, regulasi, pasar, dan teknologi. Bagaimanpun, fokus studi tersebut sering membuat bagaimana perusahaan menerapkan CE sulit diketahui. Artikel ini bertujuan mengisi kekosongan tersebut dengan menganalisis bagaimana perusahaan daur ulang mengelola CE berdasarkan faktor penghambatanya. Studi ini menggunakan pendekatan kualitatif studi kasus di tiga perusahaan yang berlokasi di Pekanbaru. Dua kasus pertama adalah pengelola limbah berbahan dasar kaleng, kertas, plastik dan limbah organik, sedangkan kasus terakhir merupakan perusahaan penyulingan oli bekas. Pengumpulan data penelitian dilakukan melalui desk evaluation, wawancara langsung, dan studi dokumen, sedangkan analisis dilakukan dengan within-case and crsoss-case. Hasil menunjukkan implementasi CE dialkukan melalui beberapa pendekatan diantaranya mengadopsi sistim ekonomi berbagi (antara perusahaan dengan pelanggan), kerjasama produksi perusahaan sejenis, dan mendorong peningkatan skill pegawai melalui pelatihan berkelanjutan.Kata kunci: Ekonomi melingkar, hambatan, strategi, studi kasus, perusahaan daur ulang